A Peregrine Soliton-Like Structure That Has Nothing to Deal With a Peregrine Breather - Finot, Christophe (Frontiers in Physics, 2021)
We report on experimental results where a temporal intensity profile presenting some of the main signatures of the Peregrine soliton (PS) is observed. However, the emergence of a highly peaked structure over a continuous background in a normally dispersive fiber cannot be linked to any PS dynamics and is mainly ascribed to the impact of Brillouin backscattering.